Radon and cancers other than lung cancer in underground miners: a collaborative analysis of 11 studies. - Darby, S; Whitley, E; Howe, G; Hutchings, S; Kusiak, R; Lubin, J; Morrison, H; Tirmarche, M; Tomásek, L; Radford, E (1995)
BACKGROUND: Exposure to the radioactive gas radon and its progeny (222Rn and its radioactive decay products) has recently been linked to a variety of cancers other than lung cancer in geographic correlation studies of domestic radon exposure and in individual cohorts of occupationally exposed miners. PURPOSE: This study was designed to characterize further the risks for cancers other than lung cancer (i.e., non-lung cancers) from atmospheric radon. METHODS: Mortality from non-lung cancer was examined in a collaborative analysis of data from 11 cohorts of underground miners in which radon-related excesses of lung cancer had been established. The study included 64,209 men who were employed in the mines for 6.4 years on average, received average cumulative exposures of 155 working-level months (WLM), and were followed for 16.9 years on average. RESULTS: For all non-lung cancers combined, mortality was close to that expected from mortality rates in the areas surrounding the mines (ratio of observed to expected deaths [O/E] = 1.01; 95% confidence interval [CI] = 0.95-1.07, based on 1179 deaths), and mortality did not increase with increasing cumulative exposure. Among 28 individual cancer categories, statistically significant increases in mortality for cancers of the stomach (O/E = 1.33; 95% CI = 1.16-1.52) and liver (O/E = 1.73; 95% CI = 1.29-2.28) and statistically significant decreases for cancers of the tongue and mouth (O/E = 0.52; 95% CI = 0.26-0.93), pharynx (O/E = 0.35; 95% CI = 0.16-0.66), and colon (O/E = 0.77; 95% CI = 0.63-0.95) were observed. For leukemia, mortality was increased in the period less than 10 years since starting work (O/E = 1.93; 95% CI = 1.19-2.95) but not subsequently. For none of these diseases was mortality significantly related to cumulative exposure. Among the remaining individual categories of non-lung cancer, mortality was related to cumulative exposure only for cancer of the pancreas (excess relative risk per WLM = 0.07%; 95% CI = 0.01-0.12) and, in the period less than 10 years since the start of employment, for other and unspecified cancers (excess relative risk per WLM = 0.22%; 95% CI = 0.08-0.37). CONCLUSIONS: The increases in mortality from stomach and liver cancers and leukemia are unlikely to have been caused by radon, since they are unrelated to cumulative exposure. The association between cumulative exposure and pancreatic cancer seems likely to be a chance finding, while the association between cumulative exposure and other and unspecified cancers was caused by deaths certified as due to carcinomatosis (widespread disseminated cancer throughout the body) that were likely to have been due to lung cancers. This study, therefore, provides considerable evidence that high concentrations of radon in air do not cause a material risk of mortality from cancers other than lung cancer. IMPLICATIONS: Protection standards for radon should continue to be based on consideration of the lung cancer risk alone.